Short Communication: Floristic composition and relationships between plant species abundance and soil properties in common hazel (Corylus avellana) mountainous forest of northern Iran - GHADER POURRAHMATI; ASADOLLAH MATAJI; HASSAN POURBABAEI; ALI SALEHI (Biodiversitas Journal of Biological Diversity, 2018)
Pourrahmati G, Mataji A, Pourbabaei H, Salehi A. 2018. Short Communication: Floristic composition and relationships between plant species abundance and soil properties in common hazel (Corylus avellana) mountainous forest of northern Iran. Biodiversitas 19: 1835-1841. Mountainous forests are valuable terrestrial ecosystems because of their useful services for the human being. Here, we explored the floristic composition and the relationships between plant species abundance distribution and soil physical and chemical properties in common hazel (Corylus avellana L.) in the mountainous forest of northern Iran. Within the forest stand, 30 quadrats (20 m × 20 m and 1 m × 1 m for woody and herbaceous species, respectively) were selectively sampled along an altitudinal range from 1300 m to 1800 m a.s.l. to assess plant species composition and abundance, and soil samples were taken to perform chemical and physical analyses. The results showed that a total of 43 herbaceous and 15 woody species belonging to 23 and 8 families were identified. The abundance of herbaceous species was significantly correlated with soil properties (pH and total N). Furthermore, the abundance of woody species had a non-significant correlation with soil properties.